Focused Ultrasound Improves NK-92MI Cells Infiltration Into Tumors - Yang, Chaopin; Du, Meng; Yan, Fei; Chen, Zhiyi (Frontiers in Pharmacology, 2019)
The main reasons affecting the adoptively NK cells treatment efficiency against solid tumor is the NK cells circulating in the blood vessels hardly enter into tumors and NK cells in vivo can’t prolong its viability in the absence of IL-2. Among different sources of NK cells, we used genetically modified NK-92MI cells, a suitable candidate which can release IL-2 to maintain its viability and overcome undesirable side effects causing from systemic administration of exogenous IL-2. In this study, we evaluated whether the combination of focused ultrasound (FUS) and microbubbles can improve adoptively NK-92MI cells infiltration into ovarian tumors through biodistribution, immunofluorescence and flow cytometry. The treatment effects using this strategy twice a week were also explored. Our results indicated that FUS and microbubbles can improve NK-92MI cells infiltration into tumor and the combination of FUS and NK-92MI cells groups had a better treatment effect compared with PBS group, but not with NK-92MI group. These results indicated further optimization of FUS assisted strategy was still needed to achieve treatment effect.